2012
DOI: 10.1364/oe.20.012021
|View full text |Cite
|
Sign up to set email alerts
|

Effective memory reduction of the novel look-up table with one-dimensional sub-principle fringe patterns in computer-generated holograms

Abstract: We propose a novel approach to massively reduce the memory of the novel look-up table (N-LUT) for computer-generated holograms by employing one-dimensional (1-D) sub-principle fringe patterns (sub-PFPs). Two-dimensional (2-D) PFPs used in the conventional N-LUT method are decomposed into a pair of 1-D sub-PFPs through a trigonometric relation. Then, these 1-D sub-PFPs are pre-calculated and stored in the proposed method, which results in a remarkable reduction of the memory of the N-LUT. Experimental results r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(22 citation statements)
references
References 12 publications
0
21
0
1
Order By: Relevance
“…Unfortunately, this causes speckle noise at reconstruction [63]. A variety of methods have been proposed for fast synthesis of CGHs as look-up table methods with pre-computed fringes [63,64], recurrence relation methods instead of directly calculating the optical path [65], introduction of wavefront recording plane [66], HS methods and many others. Hardware solutions as special-purpose computers like 'Holographic ReconstructioN (HORN)' [67] or GPU computing [32,[68][69][70] are very effective for fast calculation because the pixels on a CGH can be calculated independently.…”
Section: Methods For Computer Generation Of Holographic Fringe Patternsmentioning
confidence: 99%
“…Unfortunately, this causes speckle noise at reconstruction [63]. A variety of methods have been proposed for fast synthesis of CGHs as look-up table methods with pre-computed fringes [63,64], recurrence relation methods instead of directly calculating the optical path [65], introduction of wavefront recording plane [66], HS methods and many others. Hardware solutions as special-purpose computers like 'Holographic ReconstructioN (HORN)' [67] or GPU computing [32,[68][69][70] are very effective for fast calculation because the pixels on a CGH can be calculated independently.…”
Section: Methods For Computer Generation Of Holographic Fringe Patternsmentioning
confidence: 99%
“…In Ref. [25], it is shown that the original 2D distribution of the spherical-wave pattern can be obtained by multiplying a pair of 1D distribution functions. Therefore, only two 1D distributions need to be stored instead of the full 2D distribution for each distance.…”
Section: Point-cloud-based Synthesismentioning
confidence: 99%
“…Apart from decomposition into a pair of 1D distributions [25] or the radial interpolation [26,27] mentioned earlier, the FFT-based method has also been proposed [33]. In this method, the spherical-wave pattern is divided into small rectangular sections, each of which is approximated by a linear-phase distribution, as shown in Figure 4.…”
Section: Point-cloud-based Synthesismentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] One of them is the look-up-table (LUT) method. 1 In this method, a significant increase of the computational speed has been obtained by precalculating all fringe patterns corresponding to point-source contributions from each of the possible locations in the object volume, which are called elemental fringe patterns (EFPs), and by storing them in the LUT.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6][7][8] For further reduction of the memory, a new type of N-LUT based on one-dimensional (1-D) sub-PFPs decomposed from the conventional 2-D PFPs, which is called here 1-D N-LUT, has been proposed. 3 In this 1-D N-LUT method, the GB memory of the conventional 2-D PFPs-based N-LUT, which is called here 2-D N-LUT, could be dropped down to the order of megabyte (MB) memory. 3 In addition, for further reduction of the computational time of the N-LUT, several software and hardware methods have been proposed.…”
Section: Introductionmentioning
confidence: 99%